Respuestas

  • Usuario de Brainly
2013-12-15T12:45:27+01:00
\left \{ {{3x+4y=-10}\atop {7x-3y=-16}}\right. ==>\left \{ {{x=\frac{-4y-10}{3}}\atop {x=\frac{3y-16}{7}}}\right.\\ \\Ahora\ igualamos\\ \\ \ \frac{-4y-10}{3}=\frac{3y-16}{7}==>7\cdot(-4y-10)=3\cdot(3y-16)\\ \\-28y-70=9y-48==>-70+48=9y+28y\\ \\-22=37y\\ \\y=\frac{-22}{37}

ahora sustituimos el valor de "y" en la primera ecuación
3x+4y=-10==>3x+4(\frac{-22}{37})=-10\\ \\\frac{111x-88}{37}=-10\\ \\111x-88=-370\\ \\111x=-282\\ \\x=\frac{-282}{111}\\ \\x=\frac{-94}{37}